2015
DOI: 10.1016/j.jaci.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric severe asthma with fungal sensitization is mediated by steroid-resistant IL-33

Abstract: BackgroundThe mechanism underlying severe asthma with fungal sensitization (SAFS) is unknown. IL-33 is important in fungus-induced asthma exacerbations, but its role in fungal sensitization is unexplored.ObjectiveWe sought to determine whether fungal sensitization in children with severe therapy-resistant asthma is mediated by IL-33.MethodsEighty-two children (median age, 11.7 years; 63% male) with severe therapy-resistant asthma were included. SAFS (n = 38) was defined as specific IgE or skin prick test respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 36 publications
8
154
1
4
Order By: Relevance
“…This was also shown in a model of sensitization to fungal allergens, in which IL-33 was shown to be high in mice exposed to Alternaria allergen (Castanhinha et al, 2015). In our hands, treatment with r-sST2 to block IL-33 at the time of sensitization completely abolished eosinophilic airway inflammation, Th2-cell-associated cytokine production, and GCM particularly when administered in the period of maximal lung alveolarization.…”
Section: (Legend Continued On Next Page)supporting
confidence: 80%
See 1 more Smart Citation
“…This was also shown in a model of sensitization to fungal allergens, in which IL-33 was shown to be high in mice exposed to Alternaria allergen (Castanhinha et al, 2015). In our hands, treatment with r-sST2 to block IL-33 at the time of sensitization completely abolished eosinophilic airway inflammation, Th2-cell-associated cytokine production, and GCM particularly when administered in the period of maximal lung alveolarization.…”
Section: (Legend Continued On Next Page)supporting
confidence: 80%
“…In our hands, treatment with r-sST2 to block IL-33 at the time of sensitization completely abolished eosinophilic airway inflammation, Th2-cell-associated cytokine production, and GCM particularly when administered in the period of maximal lung alveolarization. Consistently, polymorphisms in IL1RL1, coding for ST2 (IL-33R), as well as the IL33 gene itself have been found associated with asthma and blood eosinophil counts, particularly in childhood asthma (Bøn-nelykke et al, 2014;Castanhinha et al, 2015;Gordon et al, 2016;Moffatt et al, 2010;Saglani et al, 2013;Savenije et al, 2011;Torgerson et al, 2011;Traister et al, 2015). In asthmatics, polymorphisms in IL1RL1 also control the relative abundance of the cell-bound IL-33R (ST2L) versus the soluble IL-33 receptor (sST2), that acts as a decoy receptor and antagonist of the IL-33-IL-33R axis (Grotenboer et al, 2013;Traister et al, 2015).…”
Section: (Legend Continued On Next Page)mentioning
confidence: 89%
“…We have shown that these children have evidence of worse inflammation than STRA without SAFS, despite being prescribed more treatment. 79 The innate epithelial cytokine is increased in bronchoalveolar lavage (BAL), and immunohistochemistry of bronchial biopsies also show increased IL-33-positive cells in children with SAFS, and in a neonatal Alternaria-sensitized murine model. Management is avoidance of fungal exposure as far as possible (checking any nebulizer for contamination and avoiding stables) and consideration of antifungal therapy, although it has to be said that the evidence for antifungal therapy is not compelling.…”
Section: Safs: Potential Approachesmentioning
confidence: 99%
“…Environmental exposure to smoke increases IL-6, IL-7 and IL-12 and thus lacks a Th2 fingerprint (158). In contrast, fungal sensitization with Alternaria alternata or rhinovirus-triggered asthma exacerbations are reported to stimulate increases in IL-33-mediated ILC2 numbers and Th2 cell numbers (159,160). CCR4 and CXCR3 are up-regulated in Aspergillus fumigatus-specific T cells from non-ABPA-allergic asthmatics (161).…”
Section: Response To Environmental Challengementioning
confidence: 99%